Role of Microbiome, Infection, and Inflammation in Autoimmune Diseases (Kindle, 2023)
Microorganisms found in the human gastrointestinal tract (GIT) are symbiotic under steady state conditions and have role in the homeostasis of the human host. The term microbiome is characterized by the collective genetic material contained in these microorganisms. Interestingly, even though there is a considerable variation in the diversity and abundance in the microbiota that occupy different habitats, metabolic mechanisms remain stable within healthy subjects. The composition and diversity of the microbiota vary considerably according to their region in the GIT and also vary in composition according to the age of the subject. Several factors such as diet, mode of delivery (vaginal or caesarean), consumption of antibiotics, geography, and environmental exposure affect their intraindividual variation and development. The effects of the microbiome could clarify the unidentified environmental risk factors in the development of autoimmune diseases, and it may have role in affecting the immune system and the course of the these diseases. It is now well known that pathological alterations in the intestinal microbiota (dysbiosis) can affect inflammation in the autoimmune diseases.
Keywords: Microbiome; Infection; Inflammation; Autoimmune